CREATING COMMUNICATIVE CONTEXT THROUGH THE USE OF EMOJI AND POLITENESS IN ONLINE ACADEMIC WRITTEN INTERACTIONS - MICLE, Veronica-Diana; MUDURE-IACOB, Ioana (Studia Universitatis Babeș-Bolyai Philologia, 2024)
Creating Communicative Context Through the Use of Emoji and Politeness in Online Academic Written Interactions. The current study aims to provide a glimpse into the way higher education students and language instructors establish rapports in the academic written communication framework through the use of emoji and online face-work strategies. Contextualisation cues are created in order to regulate transaction based communicative exchanges that result in positive outcomes, subsequently fostering an inclusive culture. Linguistic display of online discourse is fraught with perils that may impede on appropriate written academic interactions occurring between instructors and students. Negotiation of identity becomes a main objective, as there are differences in status, power and various degrees of communicative achievement between interactants. The study shares results obtained from a questionnaire administered to 92 Romanian undergraduate students offering a framework for embedding emoji and face-work in online identity negotiation via written communication. It aims to offer a digital pedagogical competence approach to cater for the emotional needs of learners whose identities as digital natives take additional effort to create in the context of using transversal skills. The main findings of the study suggest that emoji and face work enable foreign language students to better manipulate their self-image when communicating online. Crearea contextului comunicativ prin folosirea emoji și a politeții în interacțiuni scrise în mediul online academic. Studiul de față își propune să ofere o analiză a modului în care studenții și instructorii de limbă modernă din mediul academic stabilesc conexiuni în cadrul secvențelor de comunicare scrisă prin recurgerea la emoji și strategii de gestionare a imaginii de sine online (Engl. Face-work). Indiciile de contextualizare sunt folosite cu scopul de a regla secvențele comunicative tranzacționale asociate cu soluționări discursive pozitive, contribuind implicit la crearea unei culturi de tip inclusiv. Manifestările lingvistice ale discursului online sunt adeseori pline de substraturi potențial problematice care pot influența negativ comunicarea scrisă dintre profesori și studenți. Negocierea identității devine un obiectiv principal în contextul în care se conturează diferențe de status academic, putere decizională precum și niveluri diferite de performanță comunicativă din partea participanților. Studiul de față prezintă rezultatele obținute în urma administrării unui chestionar online studenților din învățământul academic (92 de participanți dintr-o universitate românească, nivel licență), sugerându-se un cadru în care negocierea identității online în registrul scris include emoji și strategii de gestionare a imaginii de sine. Propunerea autorilor este aceea de a oferi o abordare pedagogică a competenței digitale care sprijină nevoile emoționale ale studenților ale căror identități de nativi digitali se conturează cu un efort suplimentar în contextul folosirii competențelor transversale. Cuvinte-cheie: negocierea identității, discurs online, emoji, politețe pragmatică, strategii de gestionare a imaginii de sine, comunicare scrisă, context, învățare socio-emoțională. Article history: Received 14 March 2024; Revised 28 May 2024; Accepted 09 September 2024; Available online 30 September 2024; Available print 30 September 2024.